1997
DOI: 10.1016/s0003-9993(97)90327-0
|View full text |Cite
|
Sign up to set email alerts
|

Lipid, lipoprotein, and apolipoprotein profiles in active and sedentary men with tetraplegia

Abstract: ABSTRACT.Dallmeijer AJ, Hopman MTE, van der Woude LHV. Lipid, lipoprotein, and apolipoprotein profiles in active and sedentary men with tetraplegia. Arch Phys Med Rehabil 1997;78:1173-6.Objective: To investigate whether the risk profile of coronary heart disease (CHD) is more favorable in physically active men with tetraplegia compared with sedentary men with tetraplegia.Design: Using a cross-sectional design, the lipid and (apo)lipoprotein concentrations of 11 active and 13 sedentary men with tetraplegia were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0
2

Year Published

1999
1999
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 23 publications
3
41
0
2
Order By: Relevance
“…Expressed as weight (kg) divided by height (m 2 ), BMI allows classification of able-bodied adults as underweight, normal weight, overweight or obese, using the World Health Organization criteria in Table 2. 12 Mean BMI values in studies of persons with long-standing SCI range from 20 to 27, 5,6,10,[13][14][15][16][17][18] consistent with the classifications of normal and overweight, but inconsistent with classification based on measured percent fat mass. [4][5][6][7][8][9][10][11] One reason for the underestimation of obesity using BMI may be the potential measurement error associated with determination of weight and/or height in persons with SCI.…”
Section: Body Mass Index (Bmi) As a Marker Of Obesity In Chronic Scimentioning
confidence: 92%
See 2 more Smart Citations
“…Expressed as weight (kg) divided by height (m 2 ), BMI allows classification of able-bodied adults as underweight, normal weight, overweight or obese, using the World Health Organization criteria in Table 2. 12 Mean BMI values in studies of persons with long-standing SCI range from 20 to 27, 5,6,10,[13][14][15][16][17][18] consistent with the classifications of normal and overweight, but inconsistent with classification based on measured percent fat mass. [4][5][6][7][8][9][10][11] One reason for the underestimation of obesity using BMI may be the potential measurement error associated with determination of weight and/or height in persons with SCI.…”
Section: Body Mass Index (Bmi) As a Marker Of Obesity In Chronic Scimentioning
confidence: 92%
“…20 Despite this, recalled height has been used in a number of studies reporting BMI in subjects with chronic SCI. 5,16,17 An alternative is to measure length. Jones et al 21 reported the Pearson's correlation coefficient for height (measured by wall-mounted stadiometer) versus length (by the electronic ruler function of DXA) to be 0.996 (P ¼ 0.0001).…”
Section: Body Mass Index (Bmi) As a Marker Of Obesity In Chronic Scimentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 The e ect of physical activity on the lipid and (apo)lipoprotein pro®les in persons with SCI has, until now, only been investigated in a cross-sectional set-up. 4,5,9,10,15 More favorable risk pro®les were reported in wheelchair athletes 4,5 and moderately active subjects with tetraplegia, 9 in comparison with their sedentary counterparts. Janssen et al 10 found a positive relationship between hours sport participation per week and more favorable values of risk pro®le parameters.…”
Section: Introductionmentioning
confidence: 98%
“…11,12 Many authors suggested that the low HDL-C concentrations, and concomitant depressed levels of apolipoprotein-A1, in persons with SCI are the consequence of extremely low levels of physical activity, mainly resulting from their wheelchair dependent life. 4,5,7,9 Previous studies indeed showed that physical strain in daily life of persons with SCI was too low to maintain or improve physical ®tness. 13,14 The e ect of physical activity on the lipid and (apo)lipoprotein pro®les in persons with SCI has, until now, only been investigated in a cross-sectional set-up.…”
Section: Introductionmentioning
confidence: 99%